2014
DOI: 10.1016/j.jmarsys.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Why timing matters in a coastal sea: Trends, variability and tipping points in the Strait of Georgia, Canada

Abstract: In this paper we review available time series for the Strait of Georgia to identify trends and variability in physical and biogeochemical properties. Change is partly imported from the open ocean and partly results from processes operating at the local scale. The largest component of variation occurs at the seasonal scale, although the timing in annual cycles differs among properties. A second important component of variability is associated with cycles at the decadal (PDO) or sub-decadal scales (ENSO). Long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 102 publications
(156 reference statements)
3
38
0
Order By: Relevance
“…The freshwater discharge of approximately 9000 m 3 /s from the Fraser River drives much of the seasonal variation in surface oceanographic conditions in the northern Salish Sea (Waldichuk ). Long‐term salinity records in the Salish Sea have shown resultant trends of decreasing average salinity and increasing temperature in this region (Cummins and Masson ; Riche et al ) mirroring patterns of oceanographic change observed globally (van Vliet et al ). However, linking these environmental changes to ecosystem processes can be difficult owing to the complexity of biological responses, and is therefore an important area of future research.…”
mentioning
confidence: 86%
“…The freshwater discharge of approximately 9000 m 3 /s from the Fraser River drives much of the seasonal variation in surface oceanographic conditions in the northern Salish Sea (Waldichuk ). Long‐term salinity records in the Salish Sea have shown resultant trends of decreasing average salinity and increasing temperature in this region (Cummins and Masson ; Riche et al ) mirroring patterns of oceanographic change observed globally (van Vliet et al ). However, linking these environmental changes to ecosystem processes can be difficult owing to the complexity of biological responses, and is therefore an important area of future research.…”
mentioning
confidence: 86%
“…At present, temporal trends in the Strait of Georgia ecosystem have been better studied than those in Puget Sound and the Strait of Juan de Fuca. Over multiple decades in the Strait of Georgia, seawater and river water temperatures have increased, deep water oxygen has declined, sea level has risen, and timing of the Fraser River freshets has changed (Riche et al 2013). These changes can be organized into major regime shifts occurring in the late 1970s and mid-1990s , with a major shift in the zooplankton community in 1998-1999 (Li et al 2013) and the mean vertebrate trophic level decreasing since the 1980s (Preikshot et al 2013).…”
Section: Salish Sea Scalementioning
confidence: 99%
“…Peak flow from the Columbia River also occurs between late spring and early summer and the plume is transported either offshore in a southwest direction or onshore toward Juan de Fuca Strait [Liu et al, 2009;Hickey et al, 2010]. Both rivers are important for phytoplankton growth because of their contributions to the vertical entrainment of nutrients into the surface layer of the ocean [e.g., Lohan and Bruland, 2006;Hickey and Banas, 2008;Riche et al, 2014].…”
Section: Introductionmentioning
confidence: 99%